Competences in Education: Curricular Design Ideas from Critical and Practical-Deliberation based on Human Development and Social Transformation - Araya Muñoz, María Isabel (2011)
Educational systems in Latin America and worldwide are being required to provide highly qualified professionals, with the knowledge and abilities needed according to the scientific and technological advances. In view of such demands of the economic and productive reality, the educational systems present their curricular proposals under the flag of competencies. Such proposals have increased the contents, since functions or tasks are adapted from other contexts, based on expertise, without deeper studies on the real situation of the curricular sources. This paper demonstrates the importance of considering that an educational project based on professional competencies should be visualized as the individual’s comprehensive educational process. The competences approach is discussed from the point of view of education, which includes theory and practice, bringing closer the academic contents and the job activity, differing from the necessity of reasoning the competencies in education as a means to combine knowledge and experience. It is not only about being able to manage specific tasks in a future job, but about also finding solutions to problems that may arise in the different spheres of life. Aiming at such comprehensive vision of education, some ideas are proposed to design curricular projects based on competencies, from the practical-deliberative and critical tradition, focused on a humanist curricular concept and social transformation.